2012
DOI: 10.1371/journal.pone.0043216
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Fasciolosis Control in the Dry Cow Management: The Effect of Closantel Treatment on Milk Production

Abstract: The liver fluke Fasciola hepatica is a parasite of ruminants with a worldwide distribution and an apparent increasing incidence in EU member states. Effective control in dairy cattle is hampered by the lack of flukicides with a zero-withdrawal time for milk, leaving the dry period as the only time that preventive treatment can be applied. Here, we present the results of a blinded, randomized and placebo-controlled trial on 11 dairy herds (402 animals) exposed to F. hepatica to 1) assess the effect of closantel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…Recently, Charlier et al (44) conducted a trial on 11 dairy herds exposed to F. hepatica to assess the effect of closantel treatment at dry-off (or 80-42 d before calving in first-calving heifers) on milk production parameters. The authors found that closantel treatment resulted in a noticeable increase of 303 kg in a 305-d milk production (0.99 kg of milk/d/animal).…”
Section: Potential Impact Of Eimeria Sppmentioning
confidence: 99%
“…Recently, Charlier et al (44) conducted a trial on 11 dairy herds exposed to F. hepatica to assess the effect of closantel treatment at dry-off (or 80-42 d before calving in first-calving heifers) on milk production parameters. The authors found that closantel treatment resulted in a noticeable increase of 303 kg in a 305-d milk production (0.99 kg of milk/d/animal).…”
Section: Potential Impact Of Eimeria Sppmentioning
confidence: 99%
“…This has proved to be of benefit for the individual cow but does not appear to reduce the herd prevalence and hence has little effect on parasite transmission (Charlier et al, 2012;Knubben-Schweizer et al, 2010;Mezo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, treatment of dry cows during summer period is also advised. This appears to result in a significant increase in the milk production in the following lactation by 1 kg milk per day (Charlier et al, 2012). (C) The pasture rotation system described by Boray (1971Boray ( , 1972) (for farms with housing in winter and grazing in summer) can be utilized: dairy cows are treated with a flukicide before grazing on the pasture with snail habitat.…”
Section: Control Of Bovine Fasciolosis Based On the Location Of The Smentioning
confidence: 99%
“…Fasciola infection is prevalent across the globe, affecting humans as well as animals. [1][2][3][4][5] The parasite is transmitted by ingestion of metacercaria of Fasciola species found on the leaves of aquatic plants in contaminated fresh water. Fasciola gigantica caused endemic fasciolosis in cattle population of northern part of India.…”
Section: Introductionmentioning
confidence: 99%